Nurses’ use of smartphones for work purposes in the Philippines : predictors, outcomes, and issues - Bautista, John Robert Razote (2019)
Although there are studies that highlight how healthcare professionals use smartphones for work purposes, there is a scarcity of knowledge of this phenomenon among nurses – the largest group of healthcare professionals in a hospital. Existing studies are also theoretically and methodologically limited. To address these research gaps, this research aims to determine the factors and issues associated with nurses’ use of smartphones for work purposes in the Philippines based on a theoretical framework constructed using the Theory of Planned Behaviour, Organisational Support Theory, and IT Consumerisation Theory. First, an Exploratory Study based on in-depth interviews with 30 nurses in the Philippines was conducted. Results showed that nurses used their smartphones for communication, information seeking, and documentation purposes to facilitate clinical work. It also showed that several behavioural (i.e., instrumental and affective attitudes, injunctive and descriptive norms, perceived behavioural control, and intention) and organisational antecedents (i.e., perceived organisational support) could influence nurses’ use of smartphones for work purposes. Moreover, a relevant outcome of its use is enhanced quality of patient care. The study also uncovered some organisational issues that might affect how nurses used smartphones for work purposes. In general, results of the Exploratory Study were used to further develop Study I and Study II. Study I identified the predictors and outcome of nurses’ use of smartphones for work purposes. Hypothesis testing used structural equation modelling (SEM) of survey data from 517 staff nurses employed in 19 tertiary-level general hospitals in Metro Manila, Philippines. Exploratory and confirmatory factor analysis results showed that nurses’ use of smartphones for work purposes is operationally defined by its use for communication and information seeking purposes. Next, SEM results showed that injunctive norm and perceived behavioural control were positively associated with intention to use smartphones for work purposes. Moreover, intention was positively associated with nurses’ use of smartphones for work purposes. On the other hand, nurses’ use of smartphones for work purposes was positively associated with perceived quality of care. Results of the indirect effect analysis showed that perceived organisational support had an indirect effect on nurses’ intention to use smartphones for work purposes through injunctive norm and perceived behavioural control. Study II identified organisational issues that influence support to nurses’ use of smartphones for work purposes from the perspective of nurse administrators – one of the organisational agents where nurses derive organisational support. Nine focus groups were conducted with 43 nurse-administrators from nine randomly selected tertiary-level general hospitals that were part of Study I. The findings showed that the issues were divided on those that encouraged (i.e., problems with existing workplace technologies, absent or insufficient unit phones, insufficient unit phone credits, and unrealistic policies) or inhibited (i.e., smartphone use for non-work purposes and misinterpretation by patients) nurse administrators to support nurses’ use of smartphones for work purposes. Overall, the research findings were used to generate key recommendations on nurses’ use of smartphones in hospital settings. These recommendations can be used by hospitals to develop policies on nurses’ or healthcare professionals’ use of smartphones in hospitals.